Mindfulness Among Genetic Counselors Is Associated with Increased Empathy and Work Engagement and Decreased Burnout and Compassion Fatigue. Issue 5 (4th March 2018) - Silver, Julia; Caleshu, Colleen; Casson‐Parkin, Sylvie; Ormond, Kelly
Abstract: Genetic counselors experience high rates of compassion fatigue and an elevated risk for burnout, both of which can negatively impact patient care and retention in the profession. In other healthcare professions, mindfulness training has been successfully used to address similar negative psychological sequelae and to bolster empathy, which is the foundation of our counseling work. We aimed to assess associations between mindfulness and key professional variables, including burnout, compassion fatigue, work engagement, and empathy. Data were collected via an anonymous, online survey that included validated measures of mindfulness and these key professional variables. The survey was completed by 441 genetic counselors involved in direct patient care. Half of the respondents (50.1%) reported engaging in yoga, meditation, and/or breathing exercises. Mindfulness was positively correlated with work engagement (r = 0.24, p < 0.001) and empathy (as measured through four subscales: perspective taking ( r  = 0.15, p  = 0.002), empathic concern ( r  = 0.11, p  = 0.03), fantasy ( r  = − 0.11, p  = 0.03) and personal distress ( r  = − 0.15, p  = 0.001)). Mindfulness was negatively correlated with compassion fatigue ( r  = − 0.48, p  < 0.001) and burnout ( r  = − 0.50, p  < 0.001). Given these findings, mindfulness training may be a valuable addition to graduate and continuing education for genetic counselors. The integration of mindfulness into the genetic counseling field will likely improve professional morale and well‐being, while promoting workforce retention and bolstering the relational and counseling aspects of our clinical work.